Cumulative Effect of Psychosocial Factors in Youth on Ideal Cardiovascular Health in Adulthood. Issue 3 (20th January 2015) - Pulkki-Råback, Laura; Elovainio, Marko; Hakulinen, Christian; Lipsanen, Jari; Hintsanen, Mirka; Jokela, Markus; Kubzansky, Laura D.; Hintsa, Taina; Serlachius, Anna; Laitinen, Tomi; Pahkala, Katja; Mikkilä, Vera; et al.
<x xml:space="preserve">Abstract</x> Background— The American Heart Association has defined a new metric of ideal cardiovascular health as part of its 2020 Impact Goals. We examined whether psychosocial factors in youth predict ideal cardiovascular health in adulthood. Methods and Results— Participants were 477 men and 612 women from the nationwide Cardiovascular Risk in Young Finns Study. Psychosocial factors were measured from cohorts 3 to 18 years of age at the baseline of the study, and ideal cardiovascular health was examined 27 years later in adulthood. The summary measure of psychosocial factors in youth comprised socioeconomic factors, emotional factors, parental health behaviors, stressful events, self-regulation of the child, and social adjustment of the child. There was a positive association between a higher number of favorable psychosocial factors in youth and greater ideal cardiovascular health index in adulthood (β=0.16; P<0.001) that persisted after adjustment for age, sex, medication use, and cardiovascular risk factors in childhood (β=0.15; P<0.001). The association was monotonic, suggesting that each increment in favorable psychosocial factors was associated with improvement in cardiovascular health. Of the specific psychosocial factors, a favorable socioeconomic environment (β=0.12; P<0.001) and participants' self-regulatory behavior (β=0.07; P=0.004) were the strongest predictors of ideal cardiovascular health in adulthood. Conclusions— The findings suggest a dose-response association between favorable psychosocial factors in youth and cardiovascular health in adulthood, as defined by the American Heart Association metrics. The effect seems to persist throughout the range of cardiovascular health, potentially shifting the population distribution of cardiovascular health rather than simply having effects in a high-risk population.